2011
DOI: 10.1038/ijo.2011.158
|View full text |Cite|
|
Sign up to set email alerts
|

Safety, tolerability and sustained weight loss over 2 years with the once-daily human GLP-1 analog, liraglutide

Abstract: Objective:Having demonstrated short-term weight loss with liraglutide in this group of obese adults, we now evaluate safety/tolerability (primary outcome) and long-term efficacy for sustaining weight loss (secondary outcome) over 2 years.Design:A randomized, double-blind, placebo-controlled 20-week study with 2-year extension (sponsor unblinded at 20 weeks, participants/investigators at 1 year) in 19 European clinical research centers.Subjects:A total of 564 adults (n=90–98 per group; body mass index 30–40 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
470
2
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(527 citation statements)
references
References 28 publications
29
470
2
26
Order By: Relevance
“…Prior studies have shown that administration of GLP‐1 agonists has an impact on lipid homeostasis 72, 73, 74, 75. Liraglutide administration appears to have beneficial effects on plasma lipids and lipoproteins, including a reduction in total cholesterol, triglycerides, and low‐density lipoprotein cholesterol, and an increase in high‐density lipoprotein cholesterol 76, 77, 78. Moreover, we have demonstrated that intravenous lipid infusion induces ER stress in endothelial cells 41.…”
Section: Discussionmentioning
confidence: 60%
“…Prior studies have shown that administration of GLP‐1 agonists has an impact on lipid homeostasis 72, 73, 74, 75. Liraglutide administration appears to have beneficial effects on plasma lipids and lipoproteins, including a reduction in total cholesterol, triglycerides, and low‐density lipoprotein cholesterol, and an increase in high‐density lipoprotein cholesterol 76, 77, 78. Moreover, we have demonstrated that intravenous lipid infusion induces ER stress in endothelial cells 41.…”
Section: Discussionmentioning
confidence: 60%
“…The exaggerated release of gut hormones post RYGB has been implicated as a potential mediator of the observed changes in food preferences and weight loss. Their anorexigenic properties are already being exploited to treat obesity and gut hormones analogues are showing great promise (72)(73)(74)(75) , for example, Liraglutide 3 mg, a GLP-1 agonist, has recently been approved as an antiobesity drug in the USA and Europe. Perhaps the key to a 'medical bypass' relies on successfully mimicking the hormonal milieu of RYGB with the additive or even synergistic effects of combination gut hormones.…”
Section: Resultsmentioning
confidence: 99%
“…Monotherapy with liraglutide at a higher dose of 2.4-3.0 mg once a day induced significant and sustained weight loss, improved certain obesityrelated risk factors (especially blood pressure), and reduced the incidence of prediabetes and metabolic syndrome over 1-2 years 85,86 . Of interest, results were more favourable with liraglutide than with orlistat (120 mg three times a day orally) used as an active comparator.…”
Section: Glp-1 Receptor Agonists and Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Liraglutide 85,86 appears also to have promising effects on bodyweight in overweight/obese adults without T2DM. Monotherapy with liraglutide at a higher dose of 2.4-3.0 mg once a day induced significant and sustained weight loss, improved certain obesityrelated risk factors (especially blood pressure), and reduced the incidence of prediabetes and metabolic syndrome over 1-2 years 85,86 .…”
Section: Glp-1 Receptor Agonists and Dpp-4 Inhibitorsmentioning
confidence: 99%